ETUDE DE L’EFFICACITE DE L’EXTRAIT ETHANOLIQUE D’ECORCES DE PUNICA GRANATUM LINN SUR DEUX SOUCHES PHYTOPATHOGENES :ASCOCYHTA RABIEI (PASS.) LABR. ET FUSARIUM OXYSPORUM F.SP.RADICIS –LYCOPERSICI - Khedoudja Kanoun; Bouziane Abbouni; Mohamed Lamine Bénine; Fatima –Zohra Benmahdi; Bakhta Marouf (European Scientific Journal, ESJ, 2014)
The aim of this study is the evaluation of the antifungal activity ofPunica granatum peel towartds two phytopathogenic agents, wich are: theAscocyhta rabiei (pass .) Labr and Fusarium oxysporum f.sp . radicislycopersici(FORL). To test the effectiveness of the ethanol extract ofpomegranate peel (EEPP), three parameters were studied: the mycelialgrowth, inhibition rate and sporulation. It is thus that the strain of Fusariumoxysporum lycopersici f.sp.Radicis was more resistant to 5% EEPP withmycelial growth of 9 mm and an inhibition rate of 75.67%, compared tothose of Ascocyhta rabiei (pass). Labr with mycelial growth of 7 mm andan inhibition rate of 79.41% after 7 days of incubation. This difference ismainly due to the sensitivity and the natural resistance of the strains tested.